A novel approach to estimate methane oxidation in interim landfill covers across the USA. (2015) - Abichou, Tarek; Kormi, Tarek; Wang, Cheng; Chanton, Jeffrey P.; Green, Roger; Escobar, Francisco
This study consisted using a numerical model to simulate methane emission and oxidation through simulated interim landfill covers located in different climatic zones of the USA. Results of these simulations show that methane loading has a significant influence on methane oxidation. At low methane loading, the soil cover is able to oxidise all of the methane coming from below. At these loading rates the soil cover can oxidise 100% of the incoming methane. As for fraction oxidised, there seems to be a methane loading rate below which methane oxidation is equal to 100%. Above this methane loading, the cover is not able to oxidise all of the incoming methane. Therefore, percent oxidation starts to decrease as the methane loading increases. Fraction oxidised, for all climates was expressed as a function of the methane loading escaping the landfill gas collection system. These functions are characteristics of each climate type.